Studies on the age, growth and reproduction characteristics of the chub, Leuciscus cephalus orientalis, (Nordmann, 1840) in Karasu River, Turkey - Erdoğan, Orhan; Turkmen, Mustafa; Yıldırım, Ayhan (My University, 2002)
-
Keywords: Balıkçılık